أحكام انتهاء العقد بين المعايير الشرعية والقانون المدني البحريني Provisions for termination of a contract between Sharia standards and Bahraini civil law - Alshaikh, Hamad Farooq; Zakariyah, Habeebullah (AL HIKMAH RESEARCH & PUBLICATION CENTRE, 2023)
The research sheds light on a comparison between the provisions of the Bahraini Civil Law and the Sharia standards of the Accounting and Auditing Organization for Islamic Financial Institutions (AAOIFI) with regard to research sheds light on a comparison between the provisions of the Bahraini civil law and the Sharia standards of the Accounting and Auditing Organization for Islamic Financial Institutions (AAOIFI) with regard to the most important provisions for terminating the contract by known means such as termination, dismissal and annulment. Islamic finance to identify the size of the gap between them, in preparation for further studies in this regard due to the compliance of financial transactions applied in Islamic banks in the Kingdom of Bahrain to Sharia standards on the one hand, and the provisions of civil law on the other hand. The research relied on the qualitative approach and the comparative analytical description. The research concluded that there are many points of agreement between the two references, as they reach 50%, and there are points of disagreement by 30%, including points that were not addressed in one of the two references, 20%. The researcher also concluded that the points of difference in the provisions of terminating the contract are not essential. The researcher recommends conducting more comparative studies between local laws and Sharia standards with regard to Islamic financial formulas and products, and re-conducting a comprehensive study of Sharia standards to examine the gaps and weaknesses through which Islamic banks and their contracts may be affected. The researcher also recommends that the Accounting and Auditing Organization (AAOIFI) issue ) Special legal standards on terminating contracts and related matters, similar to the criterion of termination.